Social Media Portfolio: Mama’s Cookies By Sharleyza / Sharleyza Erayu - Erayu, Sharleyza (2021)
This portfolio is meant to record and report the requirements for the social media business task that has been assigned as part of the requisite for subject Principle of Entrepreneurship (ENT530). The social media portfolio is an assignment that necessitates students to create and do sell on Facebook. This portfolio specifically reports the development of Mama’s Cookies. For the first section of the portfolio, I attach the proof of Go-Ecommerce registration. Next, in the introduction section, I included items such as the name and address of the business, organizational chart, mission & vision, description of products and price list. Furthermore, in the Facebook section I illustrates the Facebook page layout and the business information displayed there. Meanwhile, in the “Custom URL Facebook Page” section, the number of likes gained for the business page as well as the custom Facebook URL is shown. Other three sections display the printscreen of teaser and copywriting posts. The Facebook posts are divided into two which are hard sell and soft sell posts. Finally, the social media portfolio is summarized in the conclusion section.